Conhecimento e comportamento sexual entre adolescentes de área rural e urbana de Goiás - Pires, Laurena Moreira (2014)
Cross-sectional study conducted between March 2012 and December 2013 that aimed to investigate and compare aspects of knowledge and sexual behavior among adolescents and young people living in a rural settlement in the Southwest region of the state of Goiás with urban adolescents in the municipality of Goiânia, Goiás. Participants from rural areas completed a standardized self-administered questionnaire, while the group of urban adolescents was randomly selected from the study by Oliveira (2013). Data were analyzed using SPSS version 13. A total of 69 adolescents and young settlers participated in the study, of whom 54 (78.3 %) adolescents who had at least seven years of formal study were compared with 107 urban adolescent students. It was found that there was no statistical difference between the groups considering gender, race and labor activity (p > 0.05). STD known more as the two groups were: HIV/AIDS, Syphilis and Hepatitis B. Most urban adolescents reported greater knowledge of STD (p < 0.05), with the exception of syphilis, reported by the settlers adolescents (p = 0.001). About contraceptive methods teens settlers also had lower knowledge in relation to urban, only IUDs and oral contraceptives proportions were similar ( p = 0.53 and p = 0.09, respectively) . Concerning the source of information on sexuality, the highest proportion of urban adolescents mentioned the internet (p=0.001) and boyfriend (p=0.002), while adolescents and young people mentioned the rural school (p=0.02) and mother (p=0.03). On the use of alcohol and other drugs, use of alcohol, tobacco, marijuana and crack showed no statistical difference between the proportions. In relation to sexual activity, 75 reported having initiated sexual life, 50 (47.2%) urban adolescents and 25 (46.3%) settlers. Condom use at first intercourse was similar between groups (p>0.05). In turn, the antecedent pregnancy excelled among rural adolescent group (p<0.001). The use of condoms as a contraceptive method was higher among the group of urban adolescents (p=0.04). Rural teens and young showed greater vulnerability to sexually transmitted diseases in relation to the group of urban adolescents. The study data show the need for intersectoral work, especially among the areas of health and education as the creation and maintenance of health facilities and rural schools in the county to facilitate access to information ensuring thus promoting comprehensive adolescent health and young people to reduce vulnerabilities.